Administrative responses to the land conversion issue in the four provinces of Panay Island - Cequiña, Maria Isabel Angela E
This study was conducted with the goal of identifying problems and issues in the implementation of land conversion policies in the four provinces of Panay. It aims to determine how the principles of land conversion are being utilized and how the present administration and monitoring of the processes of land conversion can be improved., The present study reveals that lack of information, financial and time constraints and extreme personalism hamper the implementation of land coversion policies. Educating tenants and landowners is the recommended solution to the problems in implementation of land conversion policies.